2012
DOI: 10.3727/096368912x640538
|View full text |Cite
|
Sign up to set email alerts
|

Hair Follicle Stem Cells Derived from Single Rat Vibrissa via Organ Culture Reconstitute Hair Follicles in Vivo

Abstract: Hair follicle stem cells (HFSCs) are potentially useful for the treatment of skin injuries and diseases. To achieve clinical application, a prerequisite must be accomplished: harvesting enough HFSCs from limited skin biopsy. The commonly used sorting approach for isolating HFSCs, however, suffers from its intrinsic disadvantages, such as requirement of large-scale skin biopsy. Here, we report an efficient organ culture method to isolate and expand rat HFSCs from limited skin biopsy and these HFSCs could recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…gsHFSCs isolation and in vitro culture procedure are illustrated in Figure 1(a). Cashmere of Shaanbei Cashmere goat in anagen and telogen showed significant morphological differences (Figure 1 of the putative gsHFSCs [29,30]. The results showed that gsHFSCs expressed the hair follicle stem cell markers ITGB1, Keratin 15 (K15) and CD34, but not Keratin 10 (K10), andin vivo Cashmere goat skin immunohistochemistry staining further indicates that these gsHFSCs are mainly located in the hair follicle structures (Figure 1(d) and Fig.…”
Section: In Vitro Isolation and Characterization Of Gshfscsmentioning
confidence: 84%
“…gsHFSCs isolation and in vitro culture procedure are illustrated in Figure 1(a). Cashmere of Shaanbei Cashmere goat in anagen and telogen showed significant morphological differences (Figure 1 of the putative gsHFSCs [29,30]. The results showed that gsHFSCs expressed the hair follicle stem cell markers ITGB1, Keratin 15 (K15) and CD34, but not Keratin 10 (K10), andin vivo Cashmere goat skin immunohistochemistry staining further indicates that these gsHFSCs are mainly located in the hair follicle structures (Figure 1(d) and Fig.…”
Section: In Vitro Isolation and Characterization Of Gshfscsmentioning
confidence: 84%
“…Interestingly, HFP cells cultured in two dimensions were not capable of follicle neogenesis [83]. Hair follicles were also successfully generated by implantation of rat vibrissae bulge stem cells [84]. Bulge stem cells from one hair follicle were sufficient to generate multiple hair follicles, sebaceous glands, and interfollicular epidermis.…”
Section: Dscs In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…have been identified in the bulge area, as well as in the hair germ. Our group isolated and expanded bulge stem cells from rat vibrissa hair follicles [101]. These cells support the hair follicle regeneration throughout adult homeostasis, and contain both quiescent stem cells and stem cells that are actively dividing, as demonstrated in several other tissues.…”
Section: Stem Cells In Epidermal Development and Homeostasismentioning
confidence: 99%